MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN MELALUI GERAK DAN LAGU DI PAUD HARAPAN INSANI DESA PULAU PERMAI KECAMATAN TAMBANG KABUPATEN KAMPAR - Ayu, Maimunah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is a classroom action research (PTK) is the research done in the classroom in order to improve or enhance the quality of teaching practices. The subject of research is PAUD Harapan Insani Desa Permai Island District of Mine which amounted to 14 people consisting of 6 boys and 8 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) How to improve gross motor skills in children aged 5-6 years in early childhood Harapan Insani namely by making class actions performed using two cycles as in one cycle there are three meetings so that the overall movement and songs applied for 6 meetings. 2) Application of the motion and the song is able to improve gross motor skills in children aged 5-6 years in early childhood Harapan Insani as gross motor skills in children increases every cycle in the first cycle obtained a value of 64.1% with the criteria pretty well (CB) and the second cycle obtained a value of 79.8% with good criterion (B). 3) The percentage increase in gross motor skills in children aged 5-6 years with the implementation of early childhood movement and song in Human Hope can be seen from the Pre cycle or before application to the second cycle. On the preliminary data obtained an average percentage of 45.1%. While the value of the first cycle to 64.1%. and the second cycle subsequent increase to the value of 79.8%. Where an increase in gross motor skills of children obtained prior to action for the first cycle increased by 42.1%. While the increase in gross motor skills in children from the first cycle to cycle II of 24.4%, and the overall increase in gross motor skills of children from the initial data to cycle II of 76.9%. Based on the research results obtained, the authors will provide some suggestions that 1) For schools that can always improve learning facilities in order to facilitate the learning process. 2) For the teacher in order to develop learning activities that motivate children more creative can improve gross motor skills in children. learning methods should attract the attention of children such as the implementation of research activities and track movement of children prefer to perform gross motor movements.Keywords : Motor ability Rough Kids, Motion And Songs